Numerical and Experimental Failure Analysis of Carbon Fiber-Reinforced Polymer-Based Pyrotechnic Separation Device - Mingfa Ren; Fei Weng; Jing Sun; Zhifeng Zhang; Zhiguo Ma; Tong Li (International Journal of Aerospace Engineering)
Current pyrotechnic separation devices are mainly made of metal materials, limiting the capacity of lightweight design in advanced launching vehicles. With the outstanding mechanical properties, such as high mass-specific strength and modulus, carbon fiber-reinforced polymers (CFRPs) have the potential to replace metal materials in pyrotechnic seperaton devices. However, to improve the seperation reliability of these pyrotechnic separation devices, there still needs further understanding on the the failure mode of CFRP composites under linear shaped charge (LSC). In this paper, cutting tests were carried out on CFRPs for the failure analysis of CFRPs under LSC, and nonlinear finite element analysis (FEA) was performed to characterize the evolution of LSC cutting in CFRPs. According to experimental simulation and numerical simulation, it can be found that the three main failure modes in CERPs while subjected to LSC jet are shear failure, delamination failure, and tensile failure. In the early cutting stage, the initial time of damage of the fiber and the matrix near the shaped charge shows less difference and the laminate is directly separated by the energy of high-speed jet. When the jet velocity decreases, the jet morphology collapses and matrix damages precede into the fiber, which would cause tensile failure mode of CFRPs. Meanwhile, the delamination in low jet speed stages is larger than that in the high jet speed stages. These studies on the failure modes of CFRPs under LSC provide important basis for the future design of CFRP-based pyrotechnic separation devices, which is important to the lightweight design of launching vehicles.